Implementasi Algoritma Rabin Karp untuk Pendeteksian Plagiat Dokumen Teks Menggunakan Konsep Similarity - Salmuasih -; Andi Sunyoto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2013)
Plagiarism is a crime, because it recognizes the work of others as personal work. Plagiarism is becoming serious problem as the rapid development of technology. Ironically acts of plagiarism is most prevalent among academics such as students and learners. In this case, the most often done is copy-paste-edit text documents. This study aims to analyze the act of plagiarism based on similarity contents of the document, such as copy&paste and disguised plagiarism. We implement strategic approach of Rabin-Karp algorithm, which is a multiple-pattern search algorithm. This algorithm is one of the best in analyzing compatibility between documents. The use of hashing techniques make the matching algorithm more efficient because it will just compare multiple digit of numbers. The final result is the percentage of similarity between documents being tested.